Microzooplankton Stoichiometric Plasticity Inferred from Modeling Mesocosm Experiments in the Peruvian Upwelling Region - Marki, Alexandra; Pahlow, Markus (Frontiers in Marine Science, 2016)
Abstract Oxygen minimum zones (OMZs) are often characterised by nitrogen-to-phosphorus (N:P) ratios far lower than the canonical Redfield ratio. Whereas the importance of variable stoichiometry in phytoplankton has long been recognised, variations in zooplankton stoichiometry have received much less attention. Here we combine observations from two shipboard mesocosm nutrient enrichment experiments with an optimality-based plankton ecosystem model, designed to elucidate the roles of different trophic levels and elemental stoichiometry. Pre-calibrated microzooplankton parameter sets represent foraging strategies of dinoflagellates and ciliates in our model. Our results suggest that remineralisation is largely driven by omnivorous ciliates and dinoflagellates, and highlight the importance of intraguild predation. We hypothesize that microzooplankton respond to changes in food quality in terms of nitrogen-to-carbon (N:C) ratios, rather than nitrogen-to-phosphorus (N:P) ratios, by allowing variations in their phosphorus-to-carbon (P:C) ratio. Our results point towards an important biogeochemical role of flexible microzooplankton stoichiometry.